GENEALOGY OF THE UTSMI FAMILY ACCORDING TO THE NARRATIVE SOURCE “THE CHRONICLE OF MAHMUD OF KHINALUG” - Polcaeva, Fatimat Abdulnetifovna; Musaev, Mahac Abdulaevic; Alibekov, Hizri Gadzievic (History, Archeology and Ethnography of the Caucasus, 2023)
Numerous critical aspects regarding the genealogy of Dagestan ruling families persist as subjects of debate to this date. Key issues of the origins of the principal Dagestan ruling houses (Nutsals, Shamkhals, Utsmis), the commencement of their reign, the etymology of their titles, and various other matters are still unresolved. Addressing these issues necessitates systematic genealogical research, incorporating the examination and interpretation of narrative sources dedicated to the genealogies of feudal families. A noteworthy contribution to this genre is the “Chronicle of Mahmud of Khinalug,” previously translated from Arabic into Russian and analyzed by specialists. In order to thoroughly explore this valuable narrative, we have undertaken a new translation of the text, developed genealogical diagrams to visualize the information. Furthermore, a comparative analysis of the two branches of the Kaitag family has been conducted, along with calculations facilitating the determination of chronological periods in the lives of the personalities mentioned in the chronicle. As part of this study, we have included two previously summarized fragments from earlier Russian translations. Notably, Sultan, the son of Sultan Muhammad, has been omitted from the genealogy due to an identified error in the preceding translation of the text. It is essential to acknowledge that the chronicle is a composite of works authored by two or more individuals. The original version traces the genealogy of the southern branch of the Utsmi family to the descendants of Muhammad Beg, who lived in the mid-15th century – a date corroborated by the author’s signature preserved in the work, indicating the year 1456/57. Subsequent additions to the text have been made, possibly on more than one occasion. In essence, this is a compilation work.